Design and Construction of SCADA System for Monitoring Voltage and Current in Automatic Transfer Switch (ATS) at the Automation Laboratory, Electrical Engineering Department, Politeknik Negeri Manado - Ariel Arya Putra; Michael Brillian Maramis; Iztiar Alamsyah Paputungan; Steven Johny Runtuwene; Antonius P.G Manginsela (International Journal Labs, 2026)
Reliable power supply is essential in educational and research laboratories, particularly for sensitive electronic equipment and automated systems. Unplanned power interruptions can result in data loss, equipment damage, and disruption of ongoing experiments. This study aims to design and implement a SCADA-integrated Automatic Transfer Switch (ATS) system to monitor voltage and current in a laboratory environment, enhancing power reliability and providing an interactive learning tool for students. The research employed a three-layer system architecture consisting of field devices, a Siemens S7-1200 PLC control layer, and a SCADA supervisory layer using Modbus TCP/IP communication. The system was tested over 50 simulated fault-and-recovery cycles with a resistive load of 3 kW. Performance metrics included transfer and retransfer times, measurement accuracy, and SCADA communication latency. Results indicated that the average transfer time was 2.31 seconds, well below the IEC Class II standard of 10 seconds, with 100% success in transfer operations. Voltage and current measurements achieved mean absolute errors of 1.4 V and 0.15 A, respectively. SCADA polling latency averaged 3.2 ms, demonstrating rapid data acquisition. The system also enhanced educational outcomes by allowing students to observe real-time power system behavior. In conclusion, the SCADA-ATS system effectively improved laboratory power reliability and provided pedagogical benefits. Future research may integrate UPS systems, reduce polling intervals, and explore hybrid energy sources for enhanced laboratory power management.